Purification trials of Tamanu (Calophyllum inophyllum L.) oil☆ - Nguyen Minh Nhat (EDP Sciences, 2021)
Tamanu (Calophyllum inophyllum L.) oil is a non-food oil used in traditional medicine, and with potential applications in the pharmaceutical and cosmetic industry. However, this oil, obtained by pressing the nuts, is being used as crude oil, in spite of a variable but large amount of non-lipids (called resin) being entrained. Although these should not be seen as impurities owing to their known bioactivity in many fields, not only they are responsible for the poisonous nature impeding human consumption in addition to bad smell, but they contribute to the poor oil quality, especially low stability and associated short shelf life. The present study aimed at purifying a crude tamanu oil sample through a combination of simple steps: deresination with ethanol, degumming using hot water, neutralization (KOH), bleaching with activated carbon, and deodorization. Ethanol 96% was more efficient for deresinating, compared to methanol, resulting in the extraction of 44–46% w/w of resin within 10 min (temperature 40 °C; oil:ethanol 1:1.5 w/v). Oil quality was checked in the industrial crude sample and in the fully refined product. The applied process strongly improved the color from dark brown to light golden yellow, decreased the acid value (62 down to 0.11 mgKOH/g of oil), and the viscosity (181 to 130 mPa.s). The saponification value was lowered from 206 to 180 mgKOH/g oil. The peroxide value was only slightly lowered from 85 to 55 mgO2/kg oil, thus pointing out the peculiar chemical nature of tamanu oil. Improving this important quality parameter would require additional research work, together with fine-tuned optimization of experimental conditions for a panel of crude oil samples; this was out of the scope of present work. This preliminary study shows that refining steps widely applied at industrial scale could help improving the quality of tamanu oil – an underused natural feedstock – for enhanced application in health and cosmetic fields.